2012
DOI: 10.1097/jto.0b013e3182653d7f
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection of EGFR T790M Mutation Using Colony Hybridization Predicts Favorable Prognosis of Patients with Lung Cancer Harboring Activating EGFR Mutation

Abstract: Our highly sensitive CH method showed that a subgroup of non-small-cell lung cancer patients with the EGFR mutation harbored the rare T790M allele before EGFR-TKI treatment. A high proportion of T790M allele may define a clinical subset with a relatively favorable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 16 publications
(24 reference statements)
4
116
4
1
Order By: Relevance
“…Choosing higher sensitivity methods may reveal more primary lung tumors carrying the resistance mutation in addition to the classic sensitizing EGFR mutation. Recent studies have shown that alternate methods reveal T790M mutations in up to 79% of EGFR-mutant primary NSCLC tumors [54,55,57,58]. Although, applying more sensitive detection methods such as NGS, dPCR or Beaming technology will provide more insight into the molecular mechanisms of tumor development and tumor progression, heterogeneity is one reason treatment relevant mutations such as T790M are missed at initial diagnosis.…”
Section: Tumor Type Genementioning
confidence: 99%
“…Choosing higher sensitivity methods may reveal more primary lung tumors carrying the resistance mutation in addition to the classic sensitizing EGFR mutation. Recent studies have shown that alternate methods reveal T790M mutations in up to 79% of EGFR-mutant primary NSCLC tumors [54,55,57,58]. Although, applying more sensitive detection methods such as NGS, dPCR or Beaming technology will provide more insight into the molecular mechanisms of tumor development and tumor progression, heterogeneity is one reason treatment relevant mutations such as T790M are missed at initial diagnosis.…”
Section: Tumor Type Genementioning
confidence: 99%
“…The T790M mutation has been detected in some patients who have not been treated with EGFR-TKIs (11)(12)(13)(14)(15)(16). Since the incidence of a T790M mutation has been reported to range from 0.02 to 0.05% in all surgically resected NSCLC patients based on studies using direct sequencing (2,17), it is difficult to clarify the association due to the T790M mutation and clinicopathological factors because of the limitation in the number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Since the incidence of a T790M mutation has been reported to range from 0.02 to 0.05% in all surgically resected NSCLC patients based on studies using direct sequencing (2,17), it is difficult to clarify the association due to the T790M mutation and clinicopathological factors because of the limitation in the number of cases. Using highly sensitive assays, the clinical impact of the minor T790M mutation in NSCLC patients with EGFR-TKI treatment has been previously investigated (11,14,15). However, the impact on EGFR-TKI-naive NSCLC patients has not been adequately investigated (12,13,16).…”
Section: Introductionmentioning
confidence: 99%
“…De novo T790M EGFR mutations have been observed in TKI-naïve patients and could predict a shorter response duration following EGFR-TKI treatment (2,3). Furthermore, the incidence of de novo T790M mutation may be more prevalent than expected due to the limited sensitivity of detection methods, such as direct sequencing (2)(3)(4)(5). Next generation EGFR-TKIs, including AZD9291, CO-1686 and HM61713, could inhibit EGFR T790M and activating mutations, and have been proven beneficial to NSCLC patients with EGFR-TKI (gefitinib or erlotinib) resistance caused by secondary T790M mutation (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%